O ipi como instrumento indutor da utilização de matéria prima reciclada objetivando a preservação do meio ambiente - Maia , Polyanna Cecília de Menezes (2014)
As the art standard. 225 CFRB/88 of the right to an ecologically balanced environment is a fundamental right, occasioning, therefore, a positive state conduct, which covers not only the executive but also the legislative and the judiciary. But the constituent divided the responsibilities between government and the community, therefore, the Government or the collectivity infringe constitutional law when they allow or omit before conduct detrimental to the environment. Over the years the world has been facing the consequences of growth and technological advancement, given that a capitalist society uses natural resources to promote economic growth. Such advances will undoubtedly encounter with the concept of sustainable development. And yet, it can be stated that contemporary society is a risk society. For despite the pursuit of effectiveness of the precautionary principle in order to minimize certain risks, the exorbitant production of solid waste prevents the current scientific knowledge of all risks. The production of solid waste is not only an Australian problem but a global problem, especially in developing countries. And still aggravating to have such a problem it is the projection of that in coming years the production of solid waste will double. Therefore the state and society in general can not remain silent on this factual context. So one alternative is to encourage the use of recycled raw materials in industrial processes, through extrafiscality IPI. Such an alternative may be able to achieve the objectives of the National Policy on Solid Waste more effectively, as the reduction and not solid waste, become more competitive recycled products and give greater effectiveness to the precepts of art. 225 of the Constitution.